2019
DOI: 10.1136/bmjgh-2019-001399
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of intermittent screening and treatment for the control of malaria in pregnancy: a cluster randomised trial in India

Abstract: BackgroundThe control of malaria in pregnancy (MiP) in India relies on testing women who present with symptoms or signs suggestive of malaria. We hypothesised that intermittent screening and treatment for malaria at each antenatal care visit (ISTp) would improve on this approach and reduce the adverse effects of MiP.MethodsA cluster randomised controlled trial comparing ISTp versus passive case detection (PCD) was conducted in Jharkhand state. Pregnant women of all parities with a gestational age of 18–28 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Health workers expressed support for ISTp in this study primarily because they believed that not all pregnant women with malaria were symptomatic, which in this context meant febrile. These beliefs are supported by the findings of the randomized trial on ISTp versus PCD, 12 and similar findings have recently been reported in Indonesia. 9 Passive case detection as a strategy requires that malaria is symptomatic and, therefore, is not effective in contexts such as Eastern India, where a large number of cases of malaria are, in fact, asymptomatic.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Health workers expressed support for ISTp in this study primarily because they believed that not all pregnant women with malaria were symptomatic, which in this context meant febrile. These beliefs are supported by the findings of the randomized trial on ISTp versus PCD, 12 and similar findings have recently been reported in Indonesia. 9 Passive case detection as a strategy requires that malaria is symptomatic and, therefore, is not effective in contexts such as Eastern India, where a large number of cases of malaria are, in fact, asymptomatic.…”
Section: Discussionsupporting
confidence: 85%
“…19 The proportion of women who reported that they were malaria positive or treated for malaria was the same in the pre-and post-implementation surveys. This is not unexpected as the prevalence of malaria was found to be very low in this setting (< 5.0% based on testing 3,300 women in a neighboring district 12 ), and less than half of women were tested, and this indicator was based on reports of women.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The results have been unfavorable. On study in a low transmission setting found no additional benefit in placental malaria to ISTp in comparison with treating symptomatic patients [72]. Another study in an endemic region demonstrated that ISTp with DP when compared with IPTp with SP had higher levels of placental malaria and adverse obstetrical outcomes [67].…”
Section: Treatmentmentioning
confidence: 98%
“…ISTp, the intermittent screening for malaria during antenatal visits using a rapid diagnostic test and treating test-positive women with an effective antimalarial drug [72], has been studied as a potential alternative to IPTp both in areas of SP and areas of low transmission where IPTp is not a recommendation. The results have been unfavorable.…”
Section: Treatmentmentioning
confidence: 99%